A cross-sectional study on knowledge, attitude, and practices regarding cervical cancer screening among women aged 21-45 years attending a tertiary care hospital in Southern India - M. Krishnamoorthy, Saranya; Natarajan, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Cervical cancer remains a leading yet preventable cause of cancer-related morbidity and mortality among women in India. Despite the availability of screening methods and human papillomavirus vaccination, utilisation remains low. Assessing gaps in knowledge, attitudes, and practices is essential to understand this discrepancy and to guide effective prevention strategies. This study assessed knowledge, attitudes, and practices related to cervical cancer screening and human papillomavirus vaccination among women aged 21-45 years. Methods: A descriptive cross-sectional study was conducted among 250 women aged 21-45 years attending the outpatient department of a tertiary care hospital in Chennai. Data were collected using a structured questionnaire. Knowledge, attitude, and practice scores were categorized using predefined score-based criteria. Data were analysed using STATA version 11.0. Associations were assessed using the chi-square test, and relationships between knowledge, attitude, and practice were evaluated using Pearson’s correlation coefficient. A p-value less than 0.05 was considered statistically significant. Results: Based on composite scoring, 52.0% of participants demonstrated poor knowledge regarding cervical cancer and its prevention, and only 31.6% were aware of screening methods. Although 46.8% had heard of the human papillomavirus vaccine, vaccination uptake was low at 2.8%. In contrast, 69.6% exhibited a positive attitude toward cervical cancer screening, while actual uptake of cervical cancer screening and HPV vaccination remained low. Knowledge showed significant positive correlations with attitude and practice, and attitude with practice, with all p-values below 0.001. Conclusions: Targeted counselling, opportunistic screening, and community education are essential to convert positive attitudes into preventive action.